Comparison of acute expansion of bioresorbable vascular scaffolds versus metallic drug‐eluting stents in different degrees of calcification: An Optical Coherence Tomography Study. Issue 5 (7th October 2016) - Ming Fam, Jiang; van Der Sijde, Johannes N; Karanasos, Antonios; Felix, Cordula; Diletti, Roberto; van Mieghem, Nicolas; de Jaegere, Peter; Zijlstra, Felix; Jan van Geuns, Robert; Regar, Evelyn
Abstract : Objectives: The acute expansion of bioresorbable vascular scaffolds (BRS) and drug‐eluting stents (DES) in lesions with different extent of calcification was compared by Optical Coherence Tomography (OCT). Background: The acute mechanical performance of polymeric BRS in calcified lesions is poorly understood. Methods: Acute device performance in lesions treated with either BRS( N  = 50) or DES ( N  = 50) was compared using Optical Coherence Tomography (OCT). According to angiographic degree of calcification the lesions were divided in three groups: no/mild, moderate and heavy calcification. Device performance was assessed with the following parameters by OCT: mean scaffold area, eccentricity index (EI), symmetry index (SI) and percentage incomplete strut apposition (ISA). Results: One hundred lesions from 85 patients (BRS/DES; 37/48) were analyzed. Scaffold area and SI were similar between BRS and DES groups in the three calcification subgroups. Compared to DES, EI in BRS was marginally lower in the no/mild calcification group (0.86 ± 0.03 versus 0.88 ± 0.03, p  = 0.018) but was similar in the moderate and heavy calcification groups. Compared to DES, percentage ISA struts in BRS was similar in the no/mild calcification group and was significantly lower in the moderate and heavy calcification groups (2.96 ± 2.36 versus 6.78 ± 4.61%, p  = 0.002 and 1.82 ± 2.40 versus 8.89 ± 8.25%, p  = 0.025 respectively). Conclusions: With adequate lesion preparation, implantation of BRS in a population reflective of clinical practice, resulted in a similar luminal gain compared to DES as measured by OCT, regardless of the degree of angiographic calcification, while acute malapposition is lower with BRS in moderately and heavily calcified lesions. The clinical significance of our findings warrants further evaluation in future studies. © 2016 Wiley Periodicals, Inc.